Volcanic activity at Bárðarbunga, Iceland, monitored with TerraSAR-X and TanDEM-X data - Jaenicke, Julia; Münzer, Ulrich; Minet, Christian; Eineder, Michael; Braun, Ludwig; Siegert, Florian; Gudmundsson, Agust (2016)
The central volcano Bárðarbunga, with a 65 km² large caldera, is located on the northwestern edge of Vatnajökull ice cap. It is connected with a 190 km long, from southwest to northeast running fissure system within the Neovolcanic Zone of Iceland. The subglacial volcano reaches a height of 2009 m a.s.l. and is covered with an up to 850 m thick ice layer. On 16 August 2014 high seismic activity had started in the area of Bárðarbunga and lasted until the end of February 2015. Three geothermal/tectonic events occurred and could be monitored continuously with TerraSAR-X and TanDEM-X radar data within the project IsViews (Iceland subglacial Volcanoes interdisciplinary early warning system). The development of a six months lasting fissure eruption in the Holuhraun glacier forefield, located 40 km northeast of Bárðarbunga, was observed with near real-time TerraSAR-X Stripmap data and TanDEM-X RawDEMs. The maximum extend of the lava field was measured to 84.5 km² and the volume to 1.48 km³. A subsidence of the ice masses within the Bárðarbunga caldera of up to 64 m occurred and was monitored with a time series of TanDEM-X data. The surficial loss of ice is calculated to 1.64 km³ and can be explained by a lowering of the magma chamber, triggered by the Holuhraun eruption. By means of TanDEM-X image differencing an 18 km long and 800 m wide fracture zone, extending from the Holuhraun eruption site towards Bárðarbunga, could be detected in a unique way. The TanDEM-X data reveals the fracture even underneath the glacier. The project research demonstrates that by means of high resolution TerraSAR-X and TanDEM-X data, it is possible to extensively monitor volcanic activity in Iceland and to assess the risk of a possible eruption.